Drei Buchdeckel, die von Georgina Beier gestaltet wurden, in einer schwarzen Mappe (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2013)
Copyright jointly or exclusively held by Iwalewahaus, CBCIU and/or Georgina Beier Estate Executor. CBCIU and Iwalewahaus identifiers currently unavailable.
Keywords: Water; Poetry; Sun; Books; Artists; Yoruba Art; Ijala